Analysis of acetabulum in children with developmental dysplasia of the hip by MRI scan. Issue 3 (January 2019) - Zhou, Ying; Ju, Li; Lou, Yue; Wang, Bo
Abstract : Abstract: To review the value of acetabular magnetic resonance imaging (MRI) in children with developmental dysplasia of the hip (DDH) of different ages. Eighty-eight medical records of children with unilateral DDH who were diagnosed and treated in our hospital between January 2010 and December 2015 were retrospectively analyzed. The affected hips were put into the case group, and the normal hips were put into the control group. All cases were further divided into 3 age groups: infant (<1 year), 16 cases; young children (1–3 years), 48 cases; and children (3–13 years), 24 cases. The differences of the acetabular depth (AD), the bony acetabular index (BAI), and the cartilaginous acetabular index (CAI) between each group were measured and compared for a linear correlation analysis. At the same time, the distribution of the acetabular cartilage in the anterosuperior, top, and posterosuperior parts (the three parts) from the two groups was measured, respectively. Measurement results from both the case and control groups were as follows: AD was 5.46 ± 2.62 mm and 9.74 ± 2.33 mm; BAI was 33.26 ± 5.49° and 23.50 ± 5.33°; and CAI was 21.04 ± 6.16° and 12.71 ± 4.83°. Differences from the two groups were statistically significant ( t = 11.94, 13.78, 9.16, P < .05); BAI and CAI were linearly correlated ( r = 0.86, 0.75, P < .05). The AD in infant, young children, and children groups from the case group were 4.26 ± 0.42 mm, 4.79 ± 1.74 mm, and 7.31 ± 2.74 mm, respectively, which was statically significant as well ( F = 11.37, P < .05). Under the same grouping criteria, BAI was recorded as 29.04 ± 5.11°, 34.56 ± 4.27°, and 33.12 ± 5.69°; CAI was recorded as 16.62 ± 5.50°, 21.79 ± 6.33°, and 20.91 ± 6.40° separately. There was a linear correlation ( r = 0.78, 0.65, P < .05) between BAI and CAI in young children and children groups. The distribution of acetabular cartilage in the above-mentioned three parts from both young children and children groups was statistically significant ( P < .05). MRI is a satisfactory imaging modality to children with DDH of different ages for the assessment of AD, BAI, CAI, and acetabular cartilage in multiple locations. It can provide ample imaging reference to clinical evaluation of the acetabulum development in DDH.